(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
The goal of potato breeding is to develop widely adaptable, highly productive cultivars that farmers would prefer. The objective of this study was to evaluate the performance and stability of potato varieties linking the preferences of smallholder farmers in rain-fed and irrigated environments. Using a randomized complete block design in three replicates, twelve potato cultivars were assessed in 10 settings in Southeast Ethiopia during the Meher and Belg seasons in 2019 and 2020. The environments, genotypes, and GEI all revealed significant differences (p<0.001) in the pooled analysis of the variance of tuber yield. The tuber yield variances for GEI, environment, and genotypic impacts were 15.48%, 7.61%, and 59.49% explained by the AMMI analysis, respectively. The environments were grouped into three distinct categories. A total of 99.6% of the variance was the cumulative contribution of PC1, PC2, PC3, PC4, and PC5 sharing 80.8%, 11.3%, 4.3%, 2.2%, and 1.0%, respectively High-yielding and widely adapted were Gera, Gudanie, Bubu, Belete, Shenkolla, Guassa, and Maracharre varieties, according to the AMMI, BLUP, GGE biplot, and WAAS. However, dynamic types that were particularly affected by environmental variations include Jalenie, Dagim, Gorebella, Awash, and Zemen. A stability measure of metric and preference based on various traits identified Gudanie and Guassa varieties. The scores of the small holder farmers were consistent throughout the test environments. The canonical correlation analysis indicated the significant association between the metric traits collected by the breeder and the small- holder farmer preferences. The study provides baseline data for potato breeding, and the varieties must be evaluated in the nation’s mega-environments for additional recommendations. Int. J. Agril. Res. Innov. Tech. 14(2): 85-98, December 2024